2009
DOI: 10.5194/cpd-5-1853-2009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sea level 400 000 years ago (MIS 11): analogue for present and future sea-level

Abstract: Abstract. Comparison of sea-levels today and 400 000 years ago (MIS 11), when the Earth's orbital characteristics were similar, may provide indications of future sea-level during the present interglacial. Evidence for former sea-levels occur on uplifting coastlines where shorelines are preserved. The sea-level term and the uplift term may be separated with an "uplift uplift correction" formula. This discovers the original sea-level at which the uplifted shoreline was fashioned. Estimates are based on average u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 93 publications
0
20
0
Order By: Relevance
“…Estimates using coral terraces and other indicators certainly suggest that sea level was higher than today in MIS 5e [ Kopp et al , ; Dutton and Lambeck , ]. Some less direct evidence suggests the same for MIS 11 [ Raymo and Mitrovica , ], although there continues to be more debate about sea level in this earlier interglacial [e.g., Hearty et al , ; Olson and Hearty , ; Bowen , ; Raymo and Mitrovica , ]. One way to explain particularly low ice volume/high sea level during interglacials would be through melting of all or part of the Greenland ice sheet.…”
Section: The Intensity Of Interglacialsmentioning
confidence: 99%
“…Estimates using coral terraces and other indicators certainly suggest that sea level was higher than today in MIS 5e [ Kopp et al , ; Dutton and Lambeck , ]. Some less direct evidence suggests the same for MIS 11 [ Raymo and Mitrovica , ], although there continues to be more debate about sea level in this earlier interglacial [e.g., Hearty et al , ; Olson and Hearty , ; Bowen , ; Raymo and Mitrovica , ]. One way to explain particularly low ice volume/high sea level during interglacials would be through melting of all or part of the Greenland ice sheet.…”
Section: The Intensity Of Interglacialsmentioning
confidence: 99%
“…MIS 11 is in fact considered the first strong interglacial through the MB. It also represents the longest-lasting warm period of the last 1.0 Ma (McManus et al, 1999;Hodell et al, 2000;Jouzel et al, 2007;Rodrigues et al, 2011;Milker et al, 2013), during which the sea level has been suggested to be up to 20 m above the current level (Hearty et al, 1999;Kindler and Hearty, 2000) or close to the Holocene high-stand (Rohling et al, 2009;Bowen, 2010). MIS 11 follows the largest amplitude transition (Termination V) of the last 500 kyr (Oppo et al, 1998;Rodrigues et al, 2011), at the end of MIS 12 known to be the strongest glacial of the last 800 kyr (Lang and Wolff, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…Morphologic evidence of late Cenozoic sea-level changes mostly documents Middle and Upper Pleistocene times (Guilcher, 1969;Johnson and Libbey, 1997;Siddal et al, 2006;Bowen, 2010;Pedoja et al, 2011Pedoja et al, , 2014Murray-Wallace and Woodroffe, 2014;Rovere et al, 2016). In fact, little is known about interglacials older than Marine Isotopic Stage 11 (MIS 11,360e420 ka); their timing, duration and number of high-stands would have remained unknown if isotope records were not partly alleviating our lack of knowledge (Emiliani, 1955;Shackleton, 1987;Waelbroeck et al, 2002;Lisiecki and Raymo, 2005;Bintanja and Van de Wal, 2008;Zachos et al, 2008;Rohling et al, 2009).…”
Section: Introductionmentioning
confidence: 99%